Migração, história e transmissão: uma família que se conta - Castilho, Maria Luiza Cobra de (2010)
This dissertation is focused on the themes of: migration, history and intergenerational transmission in a migrant family living in social vulnerability conditions, cared for by the Familia Acolhedora (FA) Welcoming Family (WF) Project, sponsored by São Paulo City´s local government. The study approached the family concept in force in a social imaginary that does not consider the plurality of the family concept and the diversity of the ways Brazilian families coexist, by not considering the various kinship relationships, both by blod and marital ties. Emphasis will be placed on the practices of circulating children in the family and on the relations between mothers, grandmothers and daughters, and the invisibility of fathers, especially in Brazilian families. The qualitative basis study heard and followed-up one family and their migrant trajectory, focusing on three generations of women that migrated to São Paulo. This research was enabled by Instituto de Terapia Familiar de São Paulo (São Paulo Family Therapy Institute), institution that executed the WF Project, in the context of caring for a young child/ grandchild along the time the boy‟s custody was withdrawn from his mother. The theoretical outline started from the complexity of the subject family and the contributions of history, anthropology, sociology, psychoanalysis and family counseling, in an attempt to surpass limits such as the articulation between the clinic and socio-political circumstances. The discussion contemplated the silence imposed on the family‟s history and its relation to the hegemonic model a nuclear married couple family that makes invisible other family practices such as circulating children in the family. The study also included the directions of migration in the studied family, considering gender issues: the place of women that migrate remove themselves from places marked by tradition and morality imposed on man and woman in their original cultures; the women, illegitimate daughters that depart in search of a man/father that would legitimize them as women/mothers, differentiating between the meaning of leaving/keeping, giving away and abandoning children in the various cultural practices and contexts. The study points out the little interest of public policies in the dynamics and singular histories of families, and the deaf-ear to practices and cultures that are not part of the hegemonic model, stigmatizing behaviors and maintaining the myth of a structured family and the myth of maternity . Finally, some considerations on the importance and difficulties of a project on a Brazilian family living in social vulnerability conditions that considers redeeming the circulation of their history, their specificities as a condition for transformation in subjectivities, enabling the development of new bonds